A high-performance lithium ion oxygen battery consisting of Li2O2 cathode and lithiated aluminum anode with nafion membrane for reduced O2 crossover. (October 2017) - Qin, Lei; Zhai, Dengyun; Lv, Wei; Yang, Wei; Huang, Jiaqiang; Yao, Shanshan; Cui, Jiang; Chong, Woon-Gie; Huang, Jian-Qiu; Kang, Feiyu; Kim, Jang-Kyo; Yang, Quan-Hong
Abstract: Lithium-oxygen batteries (LOBs) have attracted much attention because of their extraordinarily high specific energies. They possess critical weaknesses, however, such as poor cyclic stability, low energy efficiencies, as well as serious safety issues arising from the formation of lithium dendrites. Here, we report the synthesis of a long-life Li ion O2 battery (LIOB) consisting of an anode made from pre-lithiated aluminum (Al) foil and a Li2 O2 -preloaded oxygen cathode, which are both commercially available. The assembled LIOB delivers an excellent specific reversible capacity of 1000 mAh g −1 carbon for over 100 cycles at 100 mA g −1 and a maximum specific energy density of 1178 Wh kg −1 . The pre-lithiated Al foil functions as both the anode and current collector, and the stable solid electrolyte interphase layer formed on anode during pre-lithiation greatly improves the cyclic stability. In view of abundance and availability of the cathode and anode materials, the assembly strategy developed here can offer a promising route to large-scale fabrication of LIOBs for real-world applications. Graphical abstract: The Li ion O2 battery (LIOB) is fabricated using a lithium metal-free anode made from a pre-lithiated aluminum (Al) foil and a Li2 O2 -preloaded oxygen cathode. The stable SEI layer formed on anode during pre-lithiation greatly improves the cyclic stability. A number of voids created on the cathode after decomposing the pre-loaded Li2 O2 are expected to accommodate the reproduced discharge products. Together with the introduction of Nafion membrane for prohibiting O2 crossover, it delivers a remarkable energy density with excellent long-term stability for the assembled LIOBs. Highlights: The proof-of-concept of a lithium ion oxygen battery (LIOB) system has been fulfilled by the systematical design and fabrication using commercial materials. The pre-lithiated Al foil functions as both the anode and current collector, and the stable solid electrolyte interphase layer formed on the anode greatly improves the cyclic stability. Together with the use of Nafion membrane for prohibiting O2 crossover, the pre-lithiated Al anode and the Li2 O2 -preloaded cathode contribute to the remarkable energy density and excellent cyclic stability of the assembled LIOBs.